Metabolic variables associated with response to cognitive behavioural therapy for depression in females: A Canadian biomarker integration network for depression (CAN-BIND) study. (October 2021) - Jones, Brett D.M.; Levitan, Robert D.; Wang, Wei; Uher, Rudolf; Rotzinger, Susan; Foster, Jane A.; Kennedy, Sidney H.; Farzan, Faranak; Quilty, Lena C.; Kloiber, Stefan
Abstract: Introduction: Cognitive behavioural therapy (CBT) is an established first-line treatment for depression; however, it remains unclear which factors predict a positive outcome with this approach. Prior work suggests that co-morbid obesity predicts a poorer response to antidepressant medication. The current study examined whether there is an association between weight parameters and improvement of depressive symptoms with CBT. Methods: This was a secondary analysis of data from the "Clinical and Biological Markers of Response to Cognitive Behavioural Therapy for Depression – 6" (CANBIND-6; https://clinicaltrials.gov/ct2/show/NCT02883257 ) study. Adult participants (n = 41) with a diagnosis of Major Depressive Disorder (MDD) or Persistent Depressive Disorder (PDD) were recruited from an outpatient tertiary psychiatric centre in Canada. Participants completed 20 individual sessions of CBT over 16 weeks. The primary measure for treatment outcome was the Montgomery–Åsberg Depression Rating Scale (MADRS) total score at week 16. Results: Thirty-seven participants completed assessments pre and post CBT. Baseline weight parameters were not correlated with treatment response to CBT in the entire group. There was a significant sex*waist circumference (WC) (B:-1.34; p = 0.004) and sex*body mass index (BMI) interaction (B:-2.03; p:0.009). In female participants, baseline waist circumference, but not BMI, significantly predicted week 16 MADRS after controlling for age and baseline MADRS (B:0.422 p:0.049). Limitations: The major limitation of our preliminary finding is the small sample size. Conclusion: Our preliminary findings suggest that higher waist circumference may be associated with a better treatment response to CBT for depression in females. This result could be of clinical relevance and warrants further investigation in larger and independent samples.